2016
DOI: 10.1002/mds.26845
|View full text |Cite
|
Sign up to set email alerts
|

Detection of genomic rearrangements from targeted resequencing data in Parkinson's disease patients

Abstract: BackgroundThe analysis of coverage depth in next‐generation sequencing data allows the detection of gene dose alterations. We explore the frequency of such structural events in a Spanish cohort of sporadic PD cases.MethodsGene dose alterations were detected with the eXome‐Hidden Markov Model (XHMM) software from depth of coverage in resequencing data available for 38 Mendelian and other risk PD loci in 394 individuals (249 cases and 145 controls) and subsequently validated by quantitative PCR.ResultsWe identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 18 publications
1
19
2
Order By: Relevance
“…We were unable to detect any structural variants (SVs) (variations >50bp), despite previous studies reporting such variants in PD patients [3,24]. The latter study reported four individuals presenting copy-number variants (CNVs) along the GBA-GBAP1 region in a sporadic PD-cohort.…”
Section: Discussioncontrasting
confidence: 64%
“…We were unable to detect any structural variants (SVs) (variations >50bp), despite previous studies reporting such variants in PD patients [3,24]. The latter study reported four individuals presenting copy-number variants (CNVs) along the GBA-GBAP1 region in a sporadic PD-cohort.…”
Section: Discussioncontrasting
confidence: 64%
“…Among them, microdroplet-based PCR has been used for enrichment of a desired genomic region 60 and copy number variant detection has been used as an indicator of structural variants, such as large rearrangements. 38 In the specific case of the GBA gene, the presence of mutations originated from recombination events between the gene and the pseudogene, further complicating the analysis and leading to falsenegative results.…”
Section: Discussionmentioning
confidence: 99%
“…The eXome hidden Markov model (XHMM) is one of several algorithms developed for the detection of CNVs through NGS data (Fromer & Purcell, 2014;Fromer et al, 2012). XHMM has identified (potential) causative CNVs in, for example, patients with Parkinson's disease, autism spectrum disorders, and rare diseases like Joubert syndrome and very early onset inflammatory bowel disease (Kelsen et al, 2015;Koyama et al, 2017;Poultney et al, 2013;Spataro et al, 2017). The aim of this study was to assess both the diagnostic yield of our panel of H-TAD-associated genes and the prevalence of CNVs in these genes.…”
Section: Introductionmentioning
confidence: 99%